2014
DOI: 10.1007/s00396-014-3447-x
|View full text |Cite
|
Sign up to set email alerts
|

Recycling metals by controlled transfer of ionic species between complex fluids: en route to “ienaics”

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 130 publications
1
86
0
Order By: Relevance
“…An excellent extraction efficiency for certain compounds can be obtained with tailormade extractant molecules [2]. An extractant molecule is highly soluble in an organic solvent phase, but almost insoluble in an aqueous phase [3]. The high potential of such separation methods is applied in the field of nuclear waste management in procedures like the PUREX (Plutonium and Uranium Refining by EXtraction) and the DIAMEX (DIAMide EXtraction) process [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…An excellent extraction efficiency for certain compounds can be obtained with tailormade extractant molecules [2]. An extractant molecule is highly soluble in an organic solvent phase, but almost insoluble in an aqueous phase [3]. The high potential of such separation methods is applied in the field of nuclear waste management in procedures like the PUREX (Plutonium and Uranium Refining by EXtraction) and the DIAMEX (DIAMide EXtraction) process [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…
The lanthanide contraction is conceptualized traditionallyt hrough coordination chemistry.H ere we break this mold in as tructurals tudy of lanthanide ions dissolvedi na n amphiphilic liquid.T he lanthanide contractionp erturbs the weak interactions between molecular aggregates that drive mesoscale assembly and emergent behavior.T he weak interactions correlate with lanthanide ion transport properties, suggesting new strategies forr are-earth separation that exploit forces outside of the coordination sphere.
Results and Discussion
Impact of lanthanide contraction on intercluster interactions and emergentb ehaviorLike in our recent publication, [10] our investigation centers on hydrocarbon solutionso fal ipophilic diamide ligand that binds to lanthanidei ons to form an oil-soluble complex. Like in many other lipophilic solutions bearing dissolved metal complexes, [11] Ln III -diamide-oil solutionsa re prone to phase transi-[a] Dr.R.J.E llis Chemical Sciences Division, Oak Ridge NationalL aboratory Oak Ridge, Tennessee, 37831 (USA)
…”
mentioning
confidence: 99%
“…This decreases the electrostatic repulsion and allows the metalloamphiphile complexes to aggregate; a phenomenon that we recently investigated using small angle X‐ray scattering measurements . Very recently it was experimentally demonstrated that aggregates in metalloamphiphile‐in‐organic solutions are not strictly charge neutral …”
Section: Resultsmentioning
confidence: 98%
“…The migration of ions from hydrophilic to hydrophobic solvation environments is a ubiquitous phenomenon that underpins numerous natural and technological processes, from the conveyance of ions through lipid bilayers in cells, to industrial liquid–liquid ion extraction processes . In the latter, ions are partitioned between coexisting immiscible water and oil phases, with lipophilic donor ligands providing coordination sites in the oil . Central to all solution based ion transport systems are changes in complexation energy that is often viewed through the lens of coordination chemistry .…”
Section: Introductionmentioning
confidence: 99%